2010
DOI: 10.1093/hmg/ddq205
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic mouse model for uromodulin-associated kidney diseases shows specific tubulo-interstitial damage, urinary concentrating defect and renal failure

Abstract: Uromodulin-associated kidney diseases (UAKD) are autosomal-dominant disorders characterized by alteration of urinary concentrating ability, tubulo-interstitial fibrosis, hyperuricaemia and renal cysts at the cortico-medullary junction. UAKD are caused by mutations in UMOD, the gene encoding uromodulin. Although uromodulin is the most abundant protein secreted in urine, its physiological role remains elusive. Several in vitro studies demonstrated that mutations in uromodulin lead to endoplasmic reticulum (ER) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
101
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 61 publications
14
101
0
2
Order By: Relevance
“…These cells exhibit a remarkable phenotypic plasticity and functional overlap. They exert various functions depending on their phenotype and pathological context which can result in proor anti-fibrotic effects or have no effects at all (23,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Apart from a number of chemokines driving their influx and activation such as CX3CR1 (28,30,31,41), several molecules also play an important role including galectin-3 (42,43), the receptor for macrophage colony-stimulating factor (44), the Wnt pathway ligand Wnt7b (45) and interleukin 10 (46).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells exhibit a remarkable phenotypic plasticity and functional overlap. They exert various functions depending on their phenotype and pathological context which can result in proor anti-fibrotic effects or have no effects at all (23,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Apart from a number of chemokines driving their influx and activation such as CX3CR1 (28,30,31,41), several molecules also play an important role including galectin-3 (42,43), the receptor for macrophage colony-stimulating factor (44), the Wnt pathway ligand Wnt7b (45) and interleukin 10 (46).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
“…Both proteins are expressed in TECs, the latter exclusively. Mutations in both lead to renal fibrosis, and experimental studies suggest that MYH9 is important in podocyte physiology (162)(163)(164) and uromodulin in that of TECs (26,31,36,165).…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 99%
“…More recent studies have revealed UMOD expression to be exclusive to the renal epithelial cells lining the thick ascending limb of the loop of Henle and the early distal tubule (15). UMOD protein is glycosylated at 7 of its 8 potential N-glycosylation sites (16) and is glycosylphosphatidylinositol (GPI) anchored to the luminal surface of tubules, where it is cleaved into the urine at a rate of 50 to 100 milligrams per day (17), making it the most highly secreted protein in the urine of healthy individuals (18). In urine, it is found as a high-molecular-weight polymer (relative molecular weight [Mr] 1 × 10 6 to 10 × 10 6 ) and can be dissociated into monomers of roughly 95 kDa (17).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have revealed impaired trafficking of many of these mutant forms of the protein (28), suggesting that impaired trafficking and loss of secretion into the urine tie the mutations together mechanistically. Recently, investigators created a short transgenic allele expressing a mutant form of mouse UMOD under the Umod short promoter (18). The mouse with this transgene developed kidney disease, and the mutated UMOD protein was shown to localize in the ER.…”
Section: Introductionmentioning
confidence: 99%
“…Rare mutations in the uromodulin (UMOD) gene coding for uromodulin cause a dominant form of tubulointerstitial kidney disease (ADTKD) (1)(2)(3)(4)(5)(6)(7)(8), characterized by defective urinary concentrating ability, hyperuricemia, gout, and progression to ESRD (8)(9)(10). The mechanisms by which defective trafficking of mutant uromodulin leads to hyperuricemia are uncertain, but defective urine concentrating ability suggests a mechanism linked to volume contraction (5).…”
Section: Introductionmentioning
confidence: 99%